THE ETHICS AND POLITICS OF PLANT-BASED AND CULTURED MEAT - SEBO, JEFF (Les ateliers de l'éthique / The Ethics Forum, 2018)
In this paper I examine several of the moral and political questions raised by new kinds of meat. I begin by discussing the risks and harms associated with industrial animal agriculture, and I argue that plant-based meat and cultured meat are promising alternatives to conventional meat. I then explore the moral, conceptual, social, political, economic, and technical challenges that stand in the way of widespread adoption of these alternatives. For example, whether or not we achieve widespread adoption will depend on whether or not we can persuade business and political leaders to see plant-based and cultured meat as an opportunity rather than as a threat. Finally, I consider several ways of meeting these challenges, and I argue that we must be very careful if we want to avoid the kinds of problems that other, similar technological innovations such as GMOs have faced.